Julio Cortázar a study of the short fiction - Stavans, Ilan 1961- (Twayne's studies in short fiction, 1996)
Author of the internationally acclaimed novel Hopscotch (1963), Cortazar was born in Brussels, raised in Buenos Aires, and self-exiled to Europe in 1951. Although very much in vogue in the 1960s and 1970s in Europe, the United States, and Latin America, Cortazar has mysteriously fallen out of public favor since his death in 1984